A standards‐based model of system maintainability requirements. Issue 5 (14th March 2012) - Al‐Sarayreh, Khalid T.; Abran, Alain; Cuadrado‐Gallego, Juan J.
SUMMARY The nonfunctional requirements (NFR) are often captured only generically at a fairly high level, and they do not include the levels of detail necessary at this stage for the system engineers to allocate them as specific functionalities to be handled either by the software or the hardware, or a specific combination of the two. The European Cooperation for Space Standardization (ECSS) series of standards for the aerospace industry includes maintainability requirements as one of 16 types of NFR for embedded and real‐time software. A number of maintainability‐related concepts are dispersed throughout the ECSS, ISO 9126, and Institute of Electrical and Electronics Engineers standards to describe, at varying levels of detail, the various types of candidate maintainability requirements at the system, software, and hardware levels. This paper organizes these dispersed maintainability concepts into a standards‐based reference model of system maintainability requirements. The availability of this reference model can facilitate the early identification of the system maintainability‐NFR and their detailed allocation as specific maintainability functions to be handled by the specified allocation to hardware or software, or a specific combination of the two. In the absence of such a reference model, these NFR are typically handled in practice much later on in the software development life cycle, when at system testing time, users and developers find out that a number of maintainability requirements have been overlooked and additional effort has to be expended to implement them. The approach adopted in this research for the structure of this reference NFR model is based on the generic model of software functional requirements proposed in the COSMIC – ISO 19761 model, thereby allowing the functional size of such maintainability requirements allocated to software to be measured. Copyright © 2012 John Wiley & Sons, Ltd.